1991
DOI: 10.1128/mcb.11.10.5044
|View full text |Cite
|
Sign up to set email alerts
|

C/EBP-like proteins binding to the functional box-alpha and box-beta of the second enhancer of hepatitis B virus.

Abstract: The second enhancer (enhancer II) of hepatitis B virus is functionally liver specific. Located within an open reading frame of the virus and immediately upstream of the initiation sites of viral major transcripts, enhancer II furnishes a unique model for use in investigating the structure and function of an enhancer. In this study, two functional constituents, a 23-bp box-a and a 12-bp box-jI, are identified as being both necessary Control of gene transcription is in part regulated by the presence of cis-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
73
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 38 publications
1
73
1
Order By: Relevance
“…Moreover, the same sequence can also function as an upstream regulatory element activating the core promoter in a position-and orientation-dependent manner. [45][46][47] Although the precise mechanism is still unclear, our study suggested that G1721A was a useful viral marker for HCC in occult HBV carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the same sequence can also function as an upstream regulatory element activating the core promoter in a position-and orientation-dependent manner. [45][46][47] Although the precise mechanism is still unclear, our study suggested that G1721A was a useful viral marker for HCC in occult HBV carriers.…”
Section: Discussionmentioning
confidence: 99%
“…2 A) and transcription factor binding sites (Lo! pez-Cabrera et al, 1990 ;Yuh & Ting, 1991 ;Chen et al, 1995 ;Raney et al, 1997) are shown.…”
mentioning
confidence: 99%
“…The few mutations present in the upstream regulatory sequence (URS) of our promoter fragment are unlikely to exhibit a selective effect on one of the two core promoter transcripts because the URS regulates pre-C and C mRNA synthesis in a co-ordinate manner (Yuh et al, 1992). Of particular interest is the C-1653 T mutation in the URS as it is usually combined with the T-1762\A-1764 mutations, associated with fulminant hepatitis (Ogata et al, 1993 ;Hasegawa et al, 1994 ;Kaneko et al, 1995) and located in the alpha box, which is a strongly activating element of both enhancer II and core promoter (Yuh & Ting, 1991 ;Yuh et al, 1992). Interestingly, this mutation converts the alpha box binding site for C\EBP and related factors (Lo!…”
mentioning
confidence: 99%
See 2 more Smart Citations